Unified theoretical solutions for describing the crack-tip stress fields of finite specimens with mode-I crack under fully plastic conditions. (1st November 2022) - Huang, Maobo; Cai, Lixun
Highlights: Analytical solution for equivalent stress of RVE for cracked specimens is derived. Unified theoretical solutions for finite cracked specimens stress fields are derived. Stress distributions and contour lines are verified for CT and SEB specimens. Solutions are useful in fracture safety assessment without finite element analysis. Abstract: The analytical equation to express the equivalent stress of the representative volume element (RVE) is derived from the energy density equivalence. Based on the analytical expression for equivalent stress of the RVE, extensive analyses are conducted for the stress fields in the forward sector near the crack-tip of finite specimens with mode-I crack for pure power-law hardening materials. Further, unified theoretical solutions with various special functions for describing the stress fields are proposed under fully plastic and plane-strain conditions. Comparisons of radial stress distributions in various angles, angular stress distributions, and contour lines of the equivalent stress between the results predicted by the finite element analysis, HRR (Hutchinson and Rice and Rosengren) solutions, and the proposed unified theoretical solutions are performed. The excellent capability of the proposed unified theoretical solutions for predicting the crack-tip stress fields is verified.